2012
DOI: 10.3319/tao.2012.01.19.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Surface fCO2 and Sea-Air CO2 Fluxes in the Ulleung Basin of the East/Japan Sea

Abstract: Temperature, salinity, chlorophyll a, and surface CO 2 fugacity (fCO 2 ) were extensively investigated in the Ulleung Basin of the East/Japan Sea during four seasonal cruises. In spring, surface fCO 2 showed large variations ranging from 260 to 356 μatm, which were considerably lower than the atmospheric CO 2 levels. Surface fCO 2 was highest (316 to 409 μatm) in summer. The central part of the study area was undersaturated with respect to atmospheric CO 2 , while the coastal and easternmost regions were overs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
4
1
1
Order By: Relevance
“…However, the seasonal variation of f CO 2 shows that seawater is generally undersaturated with respect to the atmosphere with exception in summer (Fig. 4b) as other studies reported (Oh et al, 1999;Choi et al, 2012). Therefore, the UB serves as a sink of atmospheric CO 2 , in general.…”
Section: General Characteristics Of F Co 2 and Co 2 Flux In The Ubsupporting
confidence: 60%
See 1 more Smart Citation
“…However, the seasonal variation of f CO 2 shows that seawater is generally undersaturated with respect to the atmosphere with exception in summer (Fig. 4b) as other studies reported (Oh et al, 1999;Choi et al, 2012). Therefore, the UB serves as a sink of atmospheric CO 2 , in general.…”
Section: General Characteristics Of F Co 2 and Co 2 Flux In The Ubsupporting
confidence: 60%
“…Because the UB has strong solubility pumps and biological pumps, it is an ideal laboratory for ocean carbon uptake studies. For this reason some studies were carried out in the UB (Oh et al, 1999;Choi et al, 2011Choi et al, , 2012. In particular, it has been noted that the role of the coastal ocean in the global carbon budget has been underestimated (Wollast, 1998;Borges et al, 2005) and under debate (Cai and Dai, 2004;Thomas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The largest CO 2 flux to the ocean was estimated in winter and the lowest flux was found in summer. The annual mean CO 2 flux value of −1.53 mol m −2 year −1 estimated in this study is slightly lower than the value of CO 2 flux (−2.47 ± 1.26 mol m −2 year −1 ) reported in the Ulleung Basin of the East Sea [78]. This is due to fact that the Ulleung Basin is the most productive area in the East Sea except coastal regions, and our study area is much larger than that of [78].…”
Section: Sea-air Co2 Fluxescontrasting
confidence: 46%
“…In addition to higher biological production, lower SST values in spring compared to those in fall are also responsible for lower surface seawater ƒCO 2 values in spring. Seasonal variations of estimated ƒCO 2 values correspond well to measured seasonal changes in surface seawater ƒCO 2 in the East Sea [78]. Since the in situ data are a bit limited, only covering spring, summer, and fall, there might be high uncertainty of ƒCO 2 estimation during the winter season.…”
Section: Spatial and Temporal Distribution Of Surface Seawater ƒComentioning
confidence: 96%
“…이것은 수온이 비교적 낮은 봄철에는 울릉분지의 pCO 2 도 낮은 경향을 보이며 chlorophyll에 의한 pCO 2 변동성이 가장 크게 나타나는 것으로 해석할 수 있다 . 울릉분지는 계절에 따라 SST, chlorophyll과 pCO 2 의 관계가 다르게 나타나는 것으로 알려져 있으며 연직혼합에 의해 수온이 낮고 pCO 2 가 풍부한 물이 표층으로 올라오게 되면서 수온이 낮고 pCO 2 가 높은 상태를 보일 수 있다 (Oh et al, 1999;Choi et al, 2011;Choi et al, 2012;Kim et al, 2014 Table 2). 반면 연평균 pCO 2 의 직선 회귀로 구한 연간 pCO 2 증가율은 0.8 μatm이다 (Fig.…”
unclassified